2017
DOI: 10.1186/s13071-017-2085-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of taeniasis, cysticercosis and trichinellosis in Vietnam

Abstract: Taeniasis, cysticercosis and trichinellosis have been ranked as the most important food-borne parasites of humans in terms of public health, socioeconomic and trade impact. Despite this, information on these food-borne zoonoses in Vietnam is scarce and fragmented, and many local reports remain inaccessible to the international research community. This study aims to conduct comprehensive literature searches to report on the incidence and estimate the true prevalence of taeniasis in humans and T. solium cysticer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 44 publications
1
46
2
3
Order By: Relevance
“…Of the 37 articles reviewed in the current study, no single case of T. solium taeniosis was reported among humans in Iran. On the contrary, relatively higher infection rates have been reported in other areas across the world such as Vietnam, where up to 13% of the people in rural hotspots were reportedly infected with T. solium (Ng‐Nguyen et al, ). Given that T. solium taeniosis is transmitted to humans through consumption of pork, Islamic dietary laws which strictly forbid pork consumption among Muslims could have been responsible for the absence of T. solium taeniosis among humans in Iran.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of the 37 articles reviewed in the current study, no single case of T. solium taeniosis was reported among humans in Iran. On the contrary, relatively higher infection rates have been reported in other areas across the world such as Vietnam, where up to 13% of the people in rural hotspots were reportedly infected with T. solium (Ng‐Nguyen et al, ). Given that T. solium taeniosis is transmitted to humans through consumption of pork, Islamic dietary laws which strictly forbid pork consumption among Muslims could have been responsible for the absence of T. solium taeniosis among humans in Iran.…”
Section: Discussionmentioning
confidence: 96%
“…Taeniosis, cysticercosis and trichinellosis are well‐known foodborne parasitic diseases of humans with significant public health and economic importance (Ng‐Nguyen, Stevenson, & Traub, ), yet little is known about the prevalence of these foodborne zoonoses in Iran. Indeed, in Iran, being one of the biggest Muslim countries in the world, consumption of pork and meat from carrion is prohibited for religious reasons, while hunting of wild boar is merely authorized for the ethnic Armenians, Jews and Zoroastrians in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) A study on the risk factors of taeniasis/ cysticercosis in Vietnam reported that consuming undercooked or raw pork, raw vegetables or salads, and unboiled water are important positive factors for the spread of the disease, whereas hand washing with soap before meals and after defecation is important in its prevention. (10) The risk factors of taeniasis/cysticercosis transmission in Africa, Asia, Latin America, and Southeast Asia are generally similar, i.e. community culture, poor environmental sanitation, low level of personal hygiene, low educational level, free-roaming pigs, consumption of undercooked or raw pork, and consumption of raw vegetables or salads.…”
Section: Introductionmentioning
confidence: 99%
“…community culture, poor environmental sanitation, low level of personal hygiene, low educational level, free-roaming pigs, consumption of undercooked or raw pork, and consumption of raw vegetables or salads. (5,10) Similarly, the risk factors of taeniasis/cysticercosis transmission in Papua are associated with the consumption of undercooked pork and vegetables, low educational level on hygiene, and free-roaming pigs. (11) However, there is a need for further study on the management of pork consumption.…”
Section: Introductionmentioning
confidence: 99%